Nexus of Speaking and Writing for Enhancing Communication Skills - Sharma, Rom Nath (Lumbini Journal of Language and Literature, 2026)
This study has been carried out with the mindset that a speech is incomplete without written down. Analysis of the study is based on the study of the literatures related speaking skill and writing skill in connection to other communication skills. The aim of this paper is to investigate the ways writing helps for better speaking. Findings revealed that writing shapes for the effective speech. If speech is written before spoken, it makes the delivery more systematic and prevents the speech from being off topic or being away from the purpose. It also explored the effect of writing practice for speaking or delivering the speech. Moreover, there is positive nexus of writing and speaking as writing helps for better speaking and vice versa, and they are required for enhancing communicative competence for language development. However, there are also some differences between writing and speaking skill.